PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 178 PEKANBARU - Alim, Jesi Alexander Alim Alexander; Kurnia, Otang Kurnia; ', Nurlaili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted on April 24th to May 5nd 2015. The data shown the either learning process increased. The basic score of daily examination as 11,92% which 24 students passed and 8 students failed. The ending of daily examination was 75%  and the average was 77,34% on the passing grade. The second daily examination also increased from basic score as 17,12% which 28 students passed and 4 students failed. The ending of second daily examination was 87,5% and the average was 80,93%. Based on the explanation above it can be concluded that the implementation of problem based learning increased students’ achievement the  result of social studies of students IV grade of State Elementary School 178 Pekanbaru. Keywords : Problem Based  Learning, Students Achievement The Result Of Social Studies